Estudantes negros e práticas escolares de matriz africana - Jesus, Marcelo Siqueira de (2009)
The present study has as a main theme the analysis of the life history of six young black students from the same public night high school taking part of this research and that live at Baixada Fluminense in Belford Roxo city. Through oral interview we may interpret their life history data so as to understand the students opinion about afro-brazilian cultural performances such as: capoeira, maculelê, jongo, samba, pagode, funk, hip hop, candomblé e umbanda. What do they think about the afro-brazilian cultural performances? What are the peculiarities born by each student´s testimony to the racial relationship in their familial, school and social environment? To do so, we made use of the focused interview methodology and two conceptions: the dialectical theory about the racialism history and phenomenology aspects that study the racism consequences for black people. Resulting in the following categories: racialism, racism, eurocentrism, white ideal Ego, black myth, race and pan-africanism ( negritude ). We have used in this paper the category race through cultural value because we believe that at social science the biological aspect does not present a meaningful correct representation of the analysis. The major relevance to this study means the need to debate about the racial questions in education and in the brazilian society. The writers we reported to belong to the fields of education, anthropology, sociology, psychology and psychiatry.